A Comprehensive Analysis of the Relationship between Play Performance and Psychosocial Problems in School-Aged Children - Raúl Vigil-Dopico; Laura Delgado-Lobete; Rebeca Montes-Montes; José Antonio Prieto-Saborit (MDPI AG, 2022)
During childhood, play contributes to the physical, emotional, cognitive and social development of infants and children and may enhance future mental health. The aim of this study was to examine the relationship between play performance factors and psychosocial problems in school-aged children. A total of 142 typical Spanish children aged 5 to 9 years were included. Play performance was measured with the My Child's Play questionnaire, while the Strengths and Difficulties Questionnaire was used to evaluate internalizing and externalizing problems. The findings showed that personal, environmental and activity factors of play performance were associated with psychosocial problems and prosocial behavior in children. Moreover, children with high psychosocial difficulties reported significantly poorer play performance. As executive functioning during play was the factor that was most strongly associated with internalizing and externalizing psychosocial difficulties, it is possible that executive functions have a decisive role on both social cognition and self-regulation during play performance.